THE FUTURE WITH ARTIFICIAL INTELLIGENCE: A LITERATURE REVIEW ON THE POTENTIAL AND CHALLENGES OF AUTOMATION - Loso Judijanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The development of Artificial Intelligence (AI) has created both hope and concern about the future. On the one hand, AI has the potential to increase productivity, efficiency, and innovation in various sectors. On the other hand, AI-induced automation can also threaten the existence of human jobs, especially for routine and structured jobs. This article presents a literature review on the potentials and challenges of a future with AI. The literature review shows that to optimise the potential of AI, a comprehensive and proactive strategy is required. These include investments in education and training for new skills, policies that support workforce transition, strong regulatory frameworks to maintain security and privacy, and efforts to address bias and discrimination in AI systems. Close collaboration between humans and machines is also essential to maximise the added value that can be generated. With the right approach, the potential of AI can be harnessed to advance human well-being and provide solutions to global challenges. However, awareness and collective action from various stakeholders are needed for a fair and sustainable future transformation with AI.